The Rising Return to Non-Cognitive Skill - Per-Anders Edin; Peter Fredriksson; Martin Nybom; Björn Öckert (Institute of Labor Economics (IZA), 2017)
We examine the changes in the relative rewards to cognitive and non-cognitive skill during the time period 1992–2013. Using unique administrative data for Sweden, we document a secular increase in the returns to non-cognitive skill, which is particularly pronounced in the private sector and at the upper-end of the wage distribution. Workers with an abundance of non-cognitive skill were increasingly sorted into occupations that were intensive in: cognitive skill; as well as abstract, non-routine, social, non-automatable and offshorable tasks. Such occupations were also the types of occupations which saw greater increases in the relative return to non-cognitive skill. Moreover, we show that greater emphasis is placed on noncognitive skills in the promotion to leadership positions over time. These pieces of evidence are consistent with a framework where non-cognitive, inter-personal, skills are increasingly required to coordinate production within and across workplaces.
Keywords: J24; J31; 330; wage inequality; sorting; returns to skills; cognitive skills; noncognitive skills